The Effect of Workload, Job Satisfaction and Training on Employee Work Productivity at PT PLN Nusa Daya Ul Ketapang - Ashita Putri, Putu Marenda Dina; Suwena, Kadek Rai (Dinasti Publisher, 2025)
This study was designed to investigate the influence of workload, job satisfaction, and training on employee productivity at PT PLN Nusa Daya UL Ketapang. The research employed a quantitative approach, with the employees of PT PLN Nusa Daya UL Ketapang serving as the population. From a total of 395 employees, 100 respondents were selected as the sample using a non-probability sampling method with purposive sampling. This technique was chosen to ensure that only employees who met certain predetermined criteria, such as having recorded productivity data, were included in the analysis. Data collection was carried out through a survey method by distributing structured questionnaires to the respondents. Before conducting the analysis, the research instrument underwent several tests to ensure its accuracy and reliability, including validity, reliability, linearity, and multicollinearity tests. These tests confirmed that the instrument was consistent and capable of measuring the research variables appropriately. The data obtained were analyzed using multiple linear regression analysis, supported by the t-test, F-test, and coefficient of determination (R²). These statistical methods enabled the researcher to determine both the partial and simultaneous effects of workload, job satisfaction, and training on employee productivity. The results revealed that workload has a negative and significant effect on employee productivity, meaning that excessive workload tends to reduce performance. Meanwhile, job satisfaction and training both showed positive and significant effects, indicating that employees with higher job satisfaction and adequate training tend to achieve better productivity. In conclusion, the study emphasizes the importance of managing workload effectively while simultaneously improving job satisfaction and providing training opportunities to enhance employee productivity at PT PLN Nusa Daya UL Ketapang